PENGARUH MODEL PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN (POE) BERBANTUAN MEDIA GENIALLY TERHADAP PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR: [THE EFFECT OF THE PREDICT, OBSERVE, EXPLAIN (POE) LEARNING MODEL SUPPORTED BY GENIALLY ON ELEMENTARY SCHOOL STUDENTS’ UNDERSTANDING OF SCIENCE CONCEPTS] - Farah Rosmelia; Fitri Nuraeni; Primanita Sholihah Rosmana (Polyglot, 2026)
This study was motivated by the low level of science concept understanding among elementary school students, which is attributed to the suboptimal implementation of learning models that actively engage students in the learning process. The purpose of this study is to analyze the impact and improvement of the Predict, Observe, Explain (POE) learning model, supported by Genially media, on students’ science concept understanding. The research method used was a quasi-experimental study with a nonequivalent control group design, involving a sample of 44 students. Test data were collected from pre-tests and post-tests consisting of seven valid and reliable open-ended questions, while non-test data consisted of observation sheets and documentation. The results of the study indicate that the implementation of the Predict, Observe, Explain (POE) learning model supported by Genially media had a 42.5% effect on students’ understanding of science concepts. Furthermore, the results indicate that students’ science concept understanding in the experimental class improved more significantly than in the control class. This is evidenced by the experimental class’s pre-test average score of 50.62 increasing to 81.19 on the post-test following the implementation of the Predict, Observe, Explain (POE) learning model supported by Genially. Thus, the Predict, Observe, Explain (POE) learning model supported by Genially can be used as an alternative learning method to improve elementary school students’ understanding of science concepts. Abstrak Bahasa Indonesia Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep IPA siswa sekolah dasar yang disebabkan oleh kurang optimalnya penerapan model pembelajaran yang melibatkan siswa secara aktif dalam proses pembelajaran. Penelitian ini bertujuan untuk menganalisis pengaruh serta peningkatan model pembelajaran Predict, Observe, Explain (POE) berbantuan media Genially terhadap pemahaman konsep IPA siswa. Metode penelitian yang digunakan adalah kuasi eksperimen dengan desain nonequivalent control group dengan jumlah sampel sebanyak 44 siswa. Data tes berasal dari pre-test dan post-test berupa tujuh butir soal uraian yang telah dinyatakan valid dan layak digunakan, sedangkan data non-tes berupa lembar observasi dan dokumentasi. Hasil penelitian menunjukkan terdapat pengaruh sebesar 42,5% dari penerapan model pembelajaran Predict, Observe, Explain (POE) berbantuan media Genially terhadap pemahaman konsep IPA siswa. Selain itu, hasil penelitian menunjukkan bahwa pemahaman konsep IPA siswa pada kelas eksperimen mengalami peningkatan yang lebih baik dibandingkan kelas kontrol. Hal tersebut ditunjukkan oleh rata-rata nilai pre-test kelas eksperimen sebesar 50,62 menjadi 81,19 pada post-test setelah diterapkannya model Predict, Observe, Explain (POE) berbantuan media Genially. Dengan demikian, model pembelajaran Predict, Observe, Explain (POE) berbantuan media Genially dapat dijadikan sebagai salah satu alternatif pembelajaran untuk meningkatkan pemahaman konsep IPA siswa sekolah dasar.